Public perception of psychiatry, psychology and mental health professionals: a 15-year analysis - Domingo-Espiñeira, Javier; Varaona, Andrea; Montero, María; Lara-Abelenda, Francisco J.; Gutierrez-Rojas, Luis; Fernández del Campo, Elena Ameyugo; Rodriguez-Jimenez, Roberto; Pinto da Costa, Mariana; Ortega, Miguel A.; Alvarez-Mon, M.; Alvarez-Mon, Miguel Angel (Frontiers in Psychiatry, 2024)
Background: X (previously known as "Twitter") serves as a platform for open discussions on mental health, providing an avenue for scrutinizing public perspectives regarding psychiatry, psychology and their associated professionals. Objective: Our objective is to analyze the conversations happening on X about psychiatrists, psychologists, and their respective disciplines to understand how the public perception of these professionals and specialties has evolved over the last 15 years. Methods: We collected and analyzed all tweets posted in English or Spanish between 2007 and 2023 referring to psychiatry, psychology, neurology, mental health, psychiatrist, psychological, or neurologist using advance topic modelling and sentiment analysis. Results: A total of 403,767 tweets were analyzed, 155,217 (38%) were in English and 248,550 (62%) in Spanish. Tweets about mental health and mental health professionals and disciplines showed a consistent volume between 2011 and 2016, followed by a gradual increase from 2016 through 2022. The proportion of tweets discussing mental health doubled from 2016 to 2022, increasing from 20% to 67% in Spanish and from 15% to 45% in English. Several differences were observed on the volume of tweets overtime depending on the language they were written. Users associated each term with varied topics, such as seeking for help and recommendation for therapy, self-help resources, medication and side effects, suicide prevention, mental health in times of crisis, among others. The number of tweets mentioning these topics increased by 5-10% from 2016 to 2022, indicating a growing interest among the population. Emotional analysis showed most of the topics were associated with fear and anger. Conclusions: The increasing trend in discussions about mental health and the related professionals and disciplines over time may signify an elevated collective awareness of mental health. Gaining insights into the topics around these matters and user's corresponding emotions towards them presents an opportunity to combat the stigma surrounding mental health more effectively.